2020
DOI: 10.1021/acs.jpcc.0c00978
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of NaNO3 and KNO3 on MgO and Carbon Surfaces—Understanding the Substrate and the Length Scale Effects

Abstract: Inorganic salt-based ceramic composites have extended thermal energy storage applications particularly when the salts are used as phase change materials. The wetting behavior of interacting materials in such cases can significantly affect the formulation and manufacturing processes of the composites. Carbon is often employed in these composites, which takes the form of nanotubes or flakes, for either or both shape stabilization and heat transfer enhancement. We studied the wettability of molten NaNO 3 and KNO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…These timescales necessary for equilibration have also been observed in previous MD simulation studies 96 but have not been employed in most reference MD studies of quartz− water−scCO 2 systems to date. A more detailed analysis of equilibrium time scales is provided in Figures S2 and S3.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…These timescales necessary for equilibration have also been observed in previous MD simulation studies 96 but have not been employed in most reference MD studies of quartz− water−scCO 2 systems to date. A more detailed analysis of equilibrium time scales is provided in Figures S2 and S3.…”
Section: Methodsmentioning
confidence: 96%
“…Equilibrium configurations were then reached by running the simulation in the canonical ( NVT ) ensemble at 318 K for 20 ns, after which bulk fluid properties were isotropic and the water film between the quartz and CO 2 reached an equilibrium thickness (Figure ). These timescales necessary for equilibration have also been observed in previous MD simulation studies but have not been employed in most reference MD studies of quartz–water–scCO 2 systems to date. A more detailed analysis of equilibrium time scales is provided in Figures S2 and S3.…”
Section: Methodsmentioning
confidence: 98%
“…It is noteworthy that the parameter mixing approach was experimentally verified by Anagnostopoulos and resulted in correct contact angle for a NaNO 3 droplet on MgO slabs. 26 …”
Section: Methodsmentioning
confidence: 99%
“…The pronounced liquid/solid interface plays an important role in these systems . It was hypothesized that the reactivity enhancement could be explained quantitatively by accounting for the interfacial energy of molten salt/solid MgO in reaction thermodynamics. , While the MD simulations for nitrates on MgO were performed, it is yet unclear how the nitrate/MgO interfaces looks like, what are the interface energies, and how they change with composition of the nitrate melt, especially for the most relevant nitrates such as LiNO 3 , or eutectic mixtures. This knowledge is crucial for the in-depth understanding of the metastability in nitrate/MgO with respect to charging and discharging reactions (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a curvature-dependent surface tension has been well studied and evaluated in terms of Tolman length. Generally, smaller nanoparticle yields larger Tolman length, while high temperature reduces Tolman length. Numerous theoretical and experimental studies have shown that Tolman length satisfies thermodynamic consistency, providing a precise correction of interfacial curvature free energy. , In a polymer nanocomposite system, it is conceivable that the dielectric permittivity also exhibits a similar tendency at the curved interface. Although the concept of Tolman length is defined for understanding the curvature-dependent surface tension, it would be of great scientific value to extend this definition to dielectric materials.…”
Section: Introductionmentioning
confidence: 99%